Zinc Sulfate and α-tocopherol Supplementation Enhance Reproductive Performance in Male Albino Rats (Rattus norvegicus) With Lead Acetate Toxicity - Prastiya, Ragil Angga; Sardjito, Trilas; Agustono, Bodhi; Fikri, Faisal; Saputro, Amung Logam; Wurlina, Wurlina; Dewi, Basmala Launa; Pratiwi, Sherly Mega; Nugroho, Aras Prasetiyo; Moses, Ikechukwu Benjamin (Indonesian Journal of Pharmacy, 2024)
Metal toxicity from lead affects reproductive organ function by activating reactive oxygen species processes. This study aims to see how α-tocopherol and zinc sulfate (ZnSO4) affect gonads, liver, follicle-stimulating hormone, luteinizing hormone, spermatogenesis (the amount of spermatogonia, spermatocytes, and spermatids), and Leydig cells in male albino rats (Rattus norvegicus) exposed to lead acetate Pb(CH3COO)2. The samples used were 25 male Wistar rats aged 4 months, separated into five groups. For 30 days, all treatment groups were exposed to Pb(CH3COO)2 at a level of 50-mg/kg body weight (BW). The T1 group was given a dosage of 100-mg/kg BW of α-tocopherol. The ZnSO4 was given to the T2 group at a dose of 0.54-mg/kg BW. Meanwhile, the T3 group was given a mixture of ZnSO4 at 0.54-mg/kg BW and α-tocopherol at 100-mg/kg BW orally. ELISA test was carried out to determine the level of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in a blood plasma sample of 100 μl / 1 mg. Histopathological observations made on the liver included counting damaged cells and seminiferous tubules that included counting the amount of spermatogonia, spermatocytes, spermatids, Sertoli cells, and Leydig cells. Using SPSS 20 software, the collected data were analyzed using analysis of variance, followed by Duncan’s test with a 95% simultaneous confidence level. The highest average levels of FSH and LH in the T3 group were 3.6162 mIU/mL and 14.9658 mIU/mL. The finding showed that Pb(CH3COO)2 caused disruptions in the spermatogenesis and Leydig cell processes. Exogenous antioxidants in combination with ZnSO4 and α-tocopherol had significant effect on enhancing reproductive performance in animals exposed to Pb(CH3COO)2.